216k views
1 vote
!!!URGENT!!! Read Image Below.

!!!URGENT!!! Read Image Below.-example-1
User Tim Ogilvy
by
4.7k points

1 Answer

2 votes

Answer:


x = (6 \pm √((-6)^2 - 4(3)(8)))/(2(3))

Explanation:

Given the equation,
3x^2 - 6x + 8 = 0, the quadratic formula for solving this equation is given as:


x = (-b \pm √(b^2 - 4ac))/(2a)

Where,

a = 3

b = -6

c = 8

Plug in the above values into the quadratic formula.


x = (-(-6) \pm √((-6)^2 - 4(3)(8)))/(2(3))


x = (6 \pm √((-6)^2 - 4(3)(8)))/(2(3))

User Renato Coutinho
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.